2023
DOI: 10.1371/journal.pone.0286887
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and clinical implications of intranasal insulin on cognition in humans: A systematic review and meta-analysis

Abstract: Background Aberrant brain insulin signaling has been posited to lie at the crossroads of several metabolic and cognitive disorders. Intranasal insulin (INI) is a non-invasive approach that allows investigation and modulation of insulin signaling in the brain while limiting peripheral side effects. Objectives The objective of this systematic review and meta-analysis is to evaluate the effects of INI on cognition in diverse patient populations and healthy individuals. Methods MEDLINE, EMBASE, PsycINFO, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Studies have found that impaired brain insulin-PI3K-AKT signaling may promote neurodegeneration in Alzheimer’s disease (AD) by downregulating O-GlcNAcylation, subsequently promoting abnormal tau hyperphosphorylation and neurofibrillary degeneration ( Liu et al, 2011b ). Intravenous or intranasal insulin administration has improved memory function in both humans and animals ( Chapman et al, 2018 ; Wu et al, 2023b ), indicating that compromised insulin signaling pathways may be a primary defect linking AD and T2D.…”
Section: The Pathological Mechanisms In Elderly Diabetes Mellitusmentioning
confidence: 99%
“…Studies have found that impaired brain insulin-PI3K-AKT signaling may promote neurodegeneration in Alzheimer’s disease (AD) by downregulating O-GlcNAcylation, subsequently promoting abnormal tau hyperphosphorylation and neurofibrillary degeneration ( Liu et al, 2011b ). Intravenous or intranasal insulin administration has improved memory function in both humans and animals ( Chapman et al, 2018 ; Wu et al, 2023b ), indicating that compromised insulin signaling pathways may be a primary defect linking AD and T2D.…”
Section: The Pathological Mechanisms In Elderly Diabetes Mellitusmentioning
confidence: 99%